EFL STUDENTS' LISTENING COMPREHENSION AND THE RESPECTIVE CONSEQUENCES OF AUDIO-VISUAL MEDIA AT SENIOR HIGH SCOOL IN MEDAN - Bambang Nur Alamsyah Lubis; Irma Khoirot Daulay; Azizah Husda (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2023)
This study is to find out audio visual media has a significant effect to the students’ listening comprehension. The research applied quantitative design. The samples were 60 students which divide into two groups, namely experimental group and control group. The instrument of the study was multiple choice tests about conversations and stories. Based on the result of this research, the implementation of audio visual media have effect to students’ listening comprehension at the second year senior high school students score experimental group from 60 in pre-test up to 80 in post-test. The findings should that t-observed 4,05 t-table 1,66 , means that t-observed is higher that t-table. So , Ha is accepted and H0 is rejected audio visual media has significant effect on students’ listening comprehension.